2008
DOI: 10.1128/jcm.01739-07
|View full text |Cite
|
Sign up to set email alerts
|

Real-Time Reverse Transcription-PCR Assay for Comprehensive Detection of Human Rhinoviruses

Abstract: Human rhinoviruses (HRVs) are important contributors to respiratory disease, but their healthcare burden remains unclear, primarily because of the lack of sensitive, accurate, and convenient means of determining their causal role. To address this, we developed and clinically validated the sensitivity and specificity of a real-time reverse transcription-PCR (RT-PCR) assay targeting the viral 5 noncoding region defined by sequences obtained from all 100 currently recognized HRV prototype strains and 85 recently … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
229
1
1

Year Published

2009
2009
2019
2019

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 257 publications
(242 citation statements)
references
References 52 publications
3
229
1
1
Order By: Relevance
“…On: Thu, 10 May 2018 10:00:05 sequencing primers (Lu et al, 2008), those for the VP4/VP2 capsid protein region were 9895 and 9565 (Savolainen et al, 2002b) and those for the VP1 coding region were as described previously (Vlasak et al, 2003). The primers for an approximately 600 nt region spanning the 39 part of the 3D polymerase gene were as described previously (Savolainen et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…On: Thu, 10 May 2018 10:00:05 sequencing primers (Lu et al, 2008), those for the VP4/VP2 capsid protein region were 9895 and 9565 (Savolainen et al, 2002b) and those for the VP1 coding region were as described previously (Vlasak et al, 2003). The primers for an approximately 600 nt region spanning the 39 part of the 3D polymerase gene were as described previously (Savolainen et al, 2004).…”
Section: Methodsmentioning
confidence: 99%
“…In contrast, the two previously described one-step, realtime PCR assays have been designed for the iCycler real-time detection system (Bio-Rad; Hercules, CA). 8,9 The authors of one of these studies, 8 observed a reduction in amplification efficiency when the Applied Biosystems TaqMan One Step PCR Master Mix reagents kit was used with the iCycler real-time detection system underscoring the importance of establishing compatibility of all components of the PCR assay platform. Furthermore, most real-time assays for rhinovirus detection are twostep assays requiring a manual transfer of cDNA into PCR reactions and are consequently more cumbersome and more susceptible to contamination than a one-step PCR assay.…”
Section: Discussionmentioning
confidence: 99%
“…One-step assays have been developed for a limited number of PCR amplification platforms and chemistries and may not necessarily perform optimally with other platforms. 8 In addition, cross-reactivity with genetically similar enteroviruses has been reported with some assays. 8,9 A one-step, real-time PCR assay has not been described for the ABI Prism Sequence Detection System (Applied Biosystems; Foster City, CA) though this platform is widely used in clinical and research laboratories.…”
mentioning
confidence: 99%
See 2 more Smart Citations